Social Power Of Jim Jones’s Characterizations On Jonestown Massacre: Paradise Lost - Brenda, Ayuning (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2025)
This research is aimed at finding the social power method of the main character in Jonestowm Masscare: Paradise Lost (Cult Documentary). Social power of a charismatic leader theory served as the theoretical foundation for the writer to analyze the documentary. The character was recognized and examined utilizing note-taking procedures while collecting the data. The information is gleaned from character interactions, speech, actions, and quotations that refer to a charismatic leader’s influence on society in the documentary film. The study’s findings revealed five pieces of information about the social power exercised by the main character.